Casi-ortogonalidad y proximidad en L2 de martingalas PII en casi intervalos - Lobo Segura, Jaime (1999)
It was introduced in [2] the notion of prOcess with independent increments in near-intervals (PII), establishing the existence of a decomposition into components with certain regularity properties. In this work we deepen the study of such descomposition for a PII martingale, the components being one- parameter martingles with almost orthogonality and L2-proximity properties..